Nanoconfinement of tetraphenylethylene in zeolitic metal-organic framework for turn-on mechanofluorochromic stress sensing. (June 2022) - Zhang, Yang; Xiong, Tao; Möslein, Annika F.; Mollick, Samraj; Kachwal, Vishal; Babal, Arun Singh; Amin, Nader; Tan, Jin-Chong
Highlights: First AIE@MOF system and it possesses turn-on type mechanofluorochromism. Nanoconfinement effect under pressure restricts intramolecular vibrations of TPE. TPE@ZIF-71 shows real engineering applications potential. Abstract: Mechanofluorochromic materials are of great significance for the fabrication of innovative sensors and optoelectronics. However, efficient mechanofluorochromic materials are rarely explored due to the deficiency of existing design strategies. Here, we demonstrate the incarceration of aggregation-induced emission (AIE) materials within metal-organic framework (MOF) single crystals to construct a composite system with turn-on mechanofluorochromism. A new type of AIE@MOF material was designed: integrating a zeolitic MOF (ZIF-71) and tetraphenylethylene (TPE, a topical AIE material) to generate a TPE@ZIF-71 system with exceptional turn-on type mechanofluorochromism. Using terahertz vibrational spectroscopy, we show the unique fluorochromism mainly emanates from the enhanced nanoconfinement effect exerted by ZIF-71 host on TPE guest under pressure. Compared with pure TPE, we demonstrate the nanoconfinement in AIE@MOF not only changes the TPE's turn-off type sensing behavior to a turn-on type, but boosts the original sensitivity markedly by tenfold. Significantly, because ZIF-71 prevents the spontaneous recrystallization of TPE upon unloading, this allows TPE@ZIF-71 to record the stress history. This is the first demonstration of the Guest@MOF system combining the concepts of AIE and MOF; its promising properties and potential engineering applications will stimulate new directions pertaining to luminescent stress sensors and smart optics. Graphical abstract: Image, graphical abstract